Impact of Scoring First on Match Outcome in the Chinese Football Super League - Liu, Tianbiao; García-de-Alcaraz, Antonio; Wang, Hai; Hu, Ping; Chen, Qiu (Frontiers in Psychology, 2021)
The aim of this study was to explore the effect of scoring first on match outcomes in the Chinese Football Super League (CSL). A total of 1,116 matches in which at least one goal was scored from the 2014 to 2018 seasons were collected. Match outcomes, absolute goal differences, the minute of the first goal, match locations, and teams’ budgets were analysed. A team’s budget was measured in terms of a team’s value at the beginning of the season, and teams were clustered into two groups (high and low budget with means 50.77 and 13.77 million dollars, respectively). A descriptive analysis was conducted, and two generalized linear models (a multinomial logit model and a Poisson model) (p < 0.05) were applied. The results showed a favourable outcome for the team that scored first both in match outcome and goal difference. Regarding the teams that scored first, 66.31% won their matches, 20.70% achieved a draw and 12.99% lost. Specifically, home teams were more likely to win (13.42 %) and less likely to lose (9.52 %) or draw (3.90 %) than away teams. Home teams also had a higher likelihood of obtaining a larger goal difference. Higher budget teams were more likely to win (14.90 %) and less likely to lose (9.75 %) or draw (5.14 %) than low-budget teams. Additionally, for each minute the team scores closer to the end of the match, the average probability of winning increased by 0.0028. These findings can guide the strategies of coaches in different match scenarios according to the match location and the opponent’s quality.